2019
DOI: 10.1002/pc.25465
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐thermal activity relationship in a novel polymer/MOF‐based neutron‐shielding material

Abstract: Using epoxy resin (EP), a thermosetting polymer, as a neutron shielding material in nuclear facilities has become increasingly attractive because it is lightweight and has an excellent durability over neutron irradiation. However, it suffers from drawbacks such as reduced mechanical strength when mixed with functional fillers to improve the neutron shielding properties. In order to solve the issue, in this article, EP/gadolinium metal‐organic framework (Gd‐MOF) composites were successfully prepared, affording … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Furthermore, it is well acknowledged that the polymer chain dynamics are also greatly influenced by the presence of nanoparticles due to their intimate contact with the polymer matrix that is primarily referred to as interfacial interaction . In the case of the unfunctionalized MOF composite, there is no such interaction available in the system and the reinforced filler acts as impurities in the epoxy matrix, thus reducing overall mechanical properties of the composites . Additionally, the mechanical property of nanocomposites has been found to be potentially reduced due to the aggregation/agglomeration of the nanoparticles due to their high surface per unit volume .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is well acknowledged that the polymer chain dynamics are also greatly influenced by the presence of nanoparticles due to their intimate contact with the polymer matrix that is primarily referred to as interfacial interaction . In the case of the unfunctionalized MOF composite, there is no such interaction available in the system and the reinforced filler acts as impurities in the epoxy matrix, thus reducing overall mechanical properties of the composites . Additionally, the mechanical property of nanocomposites has been found to be potentially reduced due to the aggregation/agglomeration of the nanoparticles due to their high surface per unit volume .…”
Section: Resultsmentioning
confidence: 99%
“…50 In the case of the unfunctionalized MOF composite, there is no such interaction available in the system and the reinforced filler acts as impurities in the epoxy matrix, thus reducing overall mechanical properties of the composites. 51 Additionally, the mechanical property of nanocomposites has been found to be potentially reduced due to the aggregation/agglomeration of the nanoparticles due to their high surface per unit volume. 52 Abedini et al have reported that the presence of agglomerated MOF in the polymer reduces the mechanical properties by virtue of the chain disruption and augmented stress concertation around the agglomerated MOF particles.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…Gamage et al prepared highly hydrolytic stable MOF-5-PS by grafting polystyrene to MOF-5 crystals. However, the extent to which the polymer intrudes into the internal pores due to the extremely rapid polymerization process could not be controlled. Considering these facts, it is meaningful to develop a more efficient way for utilizing polymers to improve the stability of MOFs without sacrificing their origin gas sorption capacities.…”
Section: Introductionmentioning
confidence: 99%
“…Blending hydrogen-rich polymer matrix with high neutron cross-section absorbing elements can integrate neutron moderation and absorption. So, these materials are expected to become alternative materials for metals and concrete in nuclear facilities, such as polyethylene (PE) [ 14 , 15 ], high-density polyethylene (HDPE) [ 16 , 17 ], epoxy resin (EP) [ 18 , 19 ], ethylene propylene diene monomer (EPDM) [ 20 ] and polyimide (PI) [ 21 , 22 ], etc. Although PE and EPDM matrix have good processability, they have low thermal stability and it is difficult to use them at a temperature higher than 100 °C for a long time.…”
Section: Introductionmentioning
confidence: 99%